1998
DOI: 10.1084/jem.187.9.1373
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gag-specific Cytotoxic T Lymphocytes in Simian Immunodeficiency Virus–infected Rhesus Monkeys by Cell Staining with a Tetrameric Major Histocompatibility Complex Class I–Peptide Complex

Abstract: A tetrameric recombinant major histocompatibility complex (MHC) class I–peptide complex was used as a staining reagent in flow cytometric analyses to quantitate and define the phenotype of Gag-specific cytotoxic T lymphocytes (CTLs) in the peripheral blood of simian immunodeficiency virus macaque (SIVmac)-infected rhesus monkeys. The heavy chain of the rhesus monkey MHC class I molecule Mamu-A*01 and β2-microglobulin were refolded in the presence of an SIVmac Gag synthetic peptide (p11C, C–M) representing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
205
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(220 citation statements)
references
References 32 publications
14
205
1
Order By: Relevance
“…In the present study, we used human  2 m in place of monkey  2 m. Our results showed that the Mamu-B*1703 heavy chain could be refolded with IW9 in the presence of human  2 m. This is consistent with the previous publication (20), which also reported that the monkey MHC I heavy chain could refolded with human  2 m in construction of tetramers. The reason may be due to the high homology between human and monkey  2 m (92% identity).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we used human  2 m in place of monkey  2 m. Our results showed that the Mamu-B*1703 heavy chain could be refolded with IW9 in the presence of human  2 m. This is consistent with the previous publication (20), which also reported that the monkey MHC I heavy chain could refolded with human  2 m in construction of tetramers. The reason may be due to the high homology between human and monkey  2 m (92% identity).…”
Section: Discussionsupporting
confidence: 91%
“…The reason might be that LDA analysis depends on cell proliferation. 26 Peptide/MHC-I tetramers were intensively used for the staining of virus-specific T cells. Study with tetrameric complexes of HLA-A2/HIV gag or pol showed that 2% of CD8 + T cells were antigen specific.…”
Section: Discussionmentioning
confidence: 99%
“…7 For persistent HIV infection, the range is commonly 0.1-2% of CD8 + T cells. In persistent simian immunodeficiency virus infection in macaques, Kuroda et al 26 showed that epitope-specific T cells can account for as much as 10% of CD8 + T cells in the blood. Callan et al 27 have shown that between 7 and 44% of blood CD8 + T cells are EBV-specific in acute infection and the total number of CD8 + T cells is greatly increased, almost entirely by antigen-specific cells.…”
Section: Discussionmentioning
confidence: 99%
“…For the physical detection of SIV-specific CD8 ϩ T cells, staining was performed with pretitered, allophycocyanin-conjugated (Molecular Probes) Gag 181-189 CM9 (p11C) (CTPYDINQM)-Mamu-A*01 tetrameric complexes for 30 min at room temperature (51). One hundred thousand events were collected in the lymphocyte region (R1) and analyzed with CellQuest software and PAINT-A-GATE (BD Biosciences).…”
Section: Phenotypic and Functional Characterization Of T Cell Subsetsmentioning
confidence: 99%